Abundance and distribution of marine mammals in nearshore waters off New Jersey, USA - Whitt, Amy D.; Powell, James A.; Richardson, Alec G.; Bosyk, Jennifer R. (J. Cetacean Res. Manage., 2023)
Marine mammal abundance and distribution in New Jersey’s nearshore waters are not well known due to limited dedicated studies. The first yearround systematic surveys were conducted to determine the spatial/temporal distribution and estimate the abundance of marine mammals in this region prior to wind power development. Eight marine mammal species were observed: North Atlantic right whale (Eubalaena glacialis), humpback whale (Megaptera novaeangliae), minke whale (Balaenoptera acutorostrata), fin whale (Balaenoptera physalus), bottlenose dolphin (Tursiops truncatus), common dolphin (Delphinus delphis), harbour porpoise (Phocoena phocoena) and harbour seal (Phoca vitulina). Results indicate clear seasonal patterns in distribution and abundance. The fin whale, humpback whale and bottlenose dolphin were sighted during all seasons. The abundance of large whales in the study area was relatively low while the abundance of dolphin and porpoise species was high and largely seasonal. The bottlenose dolphin was the most abundant species; however, abundance was high only during spring and summer. Common dolphins and harbour porpoises were common in the study area during winter and spring. These baseline data will be used to assess potential environmental impacts of the construction and operation of offshore wind power facilities in this region.